2014
DOI: 10.1016/j.taap.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mixture effects at very low doses with combinations of anti-androgenic pesticides, antioxidants, industrial pollutant and chemicals used in personal care products

Abstract: Many xenobiotics have been identified as in vitro androgen receptor (AR) antagonists, but information about their ability to produce combined effects at low concentrations is missing. Such data can reveal whether joint effects at the receptor are induced at low levels and may support the prioritisation of in vivo evaluations and provide orientations for the grouping of anti-androgens in cumulative risk assessment. Combinations of 30 AR antagonists from a wide range of sources and exposure routes (pesticides, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…Both of these pathways converge on several common reproductive tissues and results from this initial study support the conclusions reached by the NAS panel in 2008 which recommended considering all chemicals that affect a common tissue in a cumulative assessment (National Academies of Science, 2008). Furthermore, the laboratories of Ulla Hass and Andreas Kortenkamp have corroborated our observations that dose addition accurately predicts the effects of mixtures of antiandrogenic chemicals on androgen-dependent reproductive development, regardless of whether the individual chemical share a mechanism of action or not (Christiansen et al, 2009; Hass et al, 2007; Metzdorff et al, 2007; Orton et al, 2014; Orton et al, 2012). They also report that mixtures of endocrine disrupting chemicals combined at environmentally-relevant dose levels induce effects greater than expected based on individual chemical doses levels (Axelstad et al, 2014; Isling et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Both of these pathways converge on several common reproductive tissues and results from this initial study support the conclusions reached by the NAS panel in 2008 which recommended considering all chemicals that affect a common tissue in a cumulative assessment (National Academies of Science, 2008). Furthermore, the laboratories of Ulla Hass and Andreas Kortenkamp have corroborated our observations that dose addition accurately predicts the effects of mixtures of antiandrogenic chemicals on androgen-dependent reproductive development, regardless of whether the individual chemical share a mechanism of action or not (Christiansen et al, 2009; Hass et al, 2007; Metzdorff et al, 2007; Orton et al, 2014; Orton et al, 2012). They also report that mixtures of endocrine disrupting chemicals combined at environmentally-relevant dose levels induce effects greater than expected based on individual chemical doses levels (Axelstad et al, 2014; Isling et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Conventional WWTPs eliminate a great amount of compounds but often show a limited reduction of micropollutant concentrations (Daughton and Ternes 1999;Kümmerer 2004). Low residual micropollutant concentrations might still cause negative effects in aquatic organisms (Wick et al 2009), such as endocrine-disrupting compounds, that are particularly of concern (Orton et al 2014;Brian et al 2007;Fent et al 2006a;Silva et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research confirmed that humans are typically exposed to complex mixtures of POPs and other pollutants, which might act synergically (Orton et al, 2013;Silva et al, 2002). Another relevant issue in the assessment of the potential effect of POPs is the timing of the exposure, and critical windows have been identified (e.g.…”
Section: Discussionmentioning
confidence: 99%